Hegemoni Dalam Cerpen Teken Pang Neken, Guru Abdi, Balian Runtag dan I Kadek Dadi Hakim Karya I Made Sugianto - Noviali, Siti; Ngurah Sulibra, I Ketut; Mulyawati R, Tjok Istri Agung (Humanis, 2021)
This research entitled "Analysis of Hegemony in the Ngipiang Jokowi Short Story Collection Book by I Made Sugianto ". This analysis aims to determine the structure and obtain a clear explanation about hegemony  in the four short stories. This study uses two theories including structural theory and hegemony theory. The methods and techniques used are divided into three types, namely; the data collection stage, the data analysis stage, and the data analysis presentation stage. The method used in data collection is the simak method accompanied by translation techniques and note-taking techniques. Then, methods and techniques use qualitative methods and analytic descriptive techniques. Then, proceed with informal methods in the stage of presenting the results of data analysis, the techniques used are inductive and deductive. The results obtained in this study include the narrative structure and form of hegemony in the four short stories. The narrative structure is divided into incidents, plot, characters and characterizations, settings, themes, and moral value. The analysis of hegemony in the four short stories is divided into two types, namely domination of power based on morals and domination of power which is suppressive. The author describes hegemony through characters and characterizations, incidents, and settings. The hegemony reflected in the four short stories is presented in two kinds, namely hegemony in verbal form and hegemony in physical form.